LEGAL REVIEW OF THE ORIGIN OF CHILDREN FROM UNREGISTERED MARRIAGES (Study of Decision No. 483/Pdt.P/2023/PA.Krs) - Khairan Nisa Mendrofa; Heriyanti; Elvira Fitriyani Pakpahan; Kartina Pakpahan (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The three objectives of this study are to: (1) ascertain the parentage of children in unregistered marriages; (2) ascertain the legal ramifications if children in a marriage are not registered under Indonesian law; and (3) ascertain the judge's legal considerations in decision Number 483/Pdt.P/2023/PA.Krs. Empirical and normative legal research are the types of research used in this study. The source and secondary legal materials employed in the data analysis were literary techniques, which were then examined using qualitative approaches. The study's findings indicate that the legal framework dictating how the parentage of children born to unregistered marriages is determined is routinely reviewed. This study makes reference to the laws governing marriage, No. 1 of 1974, and population management, No. 23 of 2006. Marriages that are both registered and unregistered are still regarded as legitimate but are subject to legal repercussions because the unregistered marriage. Marriages that aren't formally recorded with the Civil Registry office. Marriages that are not officially recognized by the Civil Registry Office have an effect on the children as well as the husband and wife legally.